Radiopathological Correlation in Diagnosis of Adnexal Lesions: A Hospital Based Comparative Study - Paudel, Nabin; Ghimire, Prasanna; Jha, Amit; Baidya, Pooja; Ghimire, Pragya Gautam; Adhikari, Hom Nath (Journal of Nepalgunj Medical College, 2022)
Introduction: Transabdominal and transvaginal ultrasound can be used in distinguishing lesions of adnexa. Transvaginal ultrasound has higher diagnostic accuracy than transabdominal ultrasound when compared with gold standard histopathology. It also provides better resolution as compared to transabdominal ultrasound. Aims: To find the diagnostic accuracy and efficacy of transvaginal and transabdominal sonographic techniques in adnexal pathologies by comparing against the gold standard of biopsy. Methods: Hospital based cross sectional comparative study done in 108 cases who underwent transabdominal and transvaginal sonography and histopathological study post operatively. Diagnostic findings of transabdominal and transvaginal sonogram were compared with the diagnosis of histopathology. Results: Of total 108 cases, most cases were benign. Sensitivity, specificity, accuracy, positive predictive value and negative predictive value for transabdominal were 63.15 %, 95.5%, 89.8%, 75% and 92.3% respectively. Sensitivity, specificity, accuracy, positive predictive value and negative predictive values of transvaginal were 73.6%, 95.5%, 91.6%, 77.7% and 94.4% respectively. Conclusion: Transvaginal sonography has higher diagnostic accuracy as compared to transabdominal ultrasonography.